Analysis of the Influence of Part-Time Work on Student Learning Activities - Muhammad Arif; Rosni Rosni; Ali Nurman; Soedirman Z; Ade Cimita (Universitas Negeri Medan, 2023)
Education is one of the necessities of life that every individual must have. One level of education is a college education. In tertiary institutions' learning process, students are inseparable from financial needs for learning needs and living standards. This need forces students to do part-time jobs. Part-time jobs are growing from time to time. Part-time work has both positive and negative effects on student development in the world of work. This study aims to analyze part-time jobs for students of the 2017 Geography Education Department, their relation to learning activities, and the factors that motivate students to work part-time. This study uses a quantitative approach with simple analytical techniques. The population in this study were all students of the 2017 class of the Geography Education Department, with a sample of 20 students. Data collection techniques using a questionnaire. The study results show a significant effect of part-time work and learning activities with a substantial value of 0.037 <0.05. The main factor for students is working part-time because of the financial need for college needs and the standard of living. Part-time jobs done by students are online motorcycle taxi drivers, shopkeepers, salespeople, private tutors, and web programmers.Keywords: Part-Time, Student, Geography Education, Learning Activities